Failed Dermal Allograft Procedures in Irreparable Rotator Cuff Tears Can Still Improve Pain and Function. The "Biologic Tuberoplasty Effect". Issue 7 (30th July 2018) - Mirzayan, Raffy; Stone, Michael Allan; Batech, Michael; Acevedo, Daniel; Singh, Anshu
Objectives: Massive rotator cuff tears (MRCT) are a challenging problem. Dermal allografts have been used in "bridging" procedures and superior capsule reconstruction (SCR). Both have led to clinical improvement, but without correlation with post-operative imaging. The purpose of this study is to examine graft integrity on MRI in patients who underwent an SCR or bridging procedure to determine if graft integrity correlates with functional outcome. We also propose a new classification of dermal allograft re-tear on MRI. Methods: This study was approved by our IRB. Between 2006 and 2016, 11 patients (12 shoulders) underwent a bridging procedure and 10 patients underwent an SCR for MRCT with a dermal allograft by a single surgeon. The grafts were secured to the tuberosity in a double-row, trans-osseous equivalent (DR-TOE) fashion. Pre- and post-operative VAS, acromiohumeral distance (AHD), and ASES scores, and pre-operative Hamada grade and Goutallier classification were prospectively collected and retrospectively reviewed. An MRI was obtained on all patients post-operatively to assess graft integrity. The status of the graft was divided into three types based on MRI findings:Type 1 - Graft intact medially (rim of cuff or glenoid) AND laterally (greater tuberosity);Type 2 - Graft intact laterally but torn medially;Type 3 - Graft torn laterally. The shoulders were then grouped based on these types for further analysis. Results: The average age was 61 (range: 49-73). Average follow-up was 21.6 months (range: 8-80). Average length from surgery to MRI was 13.9 months (range: 6-80). There was a significant improvement in VAS (pre-8.1 to post-1.3) and ASES (pre-26.3 to post-84.6) inType 1 (P<0.01) and in VAS (pre-7.0 to post-0.7) and ASES (pre-32.6 to post-91.2) inType 2 (P<0.01). There was no difference in post-operative VAS (1.3 vs 0.7) and ASES (84.6 vs 91.2) betweenType 1 andType 2 (P=0.8). There was no improvement in VAS (pre-7.3 vs post-5.7) and ASES (pre-30.6 vs post-37.2) inType 3 . There was a significant difference in post-operative VAS (5.7 vs 1) and ASES (37.2 vs 88.1) betweenType 3 versusTypes 1+2, respectively (P<0.01). The AHD decreased in type 3 (pre-7.8 mm to post-3.2 mm, P=0.02) but did not change inTypes 1+2 (pre-7.8 mm to post-8.0 mm, P=0.7). Conclusion: In patients who have SCR or "bridging" procedures for MRCT with a dermal allograft, there is significant improvement in VAS and ASES scores if the graft heals to the tuberosity, regardless if it is still intact to the glenoid (in SCR) or the rim of rotator cuff tendon ("bridging"). Individuals whose graft is torn from the tuberosity did not have improvement in VAS or ASES scores versus baseline. There was no significant difference in AHD in all groups. We believe that the dermal graft acts as a "biologic (interpositional) tuberoplasty, " preventing bone-to-bone contact between the tuberosity and the acromion, thus eliminating pain and improving function. We still recommend performing an SCR when indicated because it has been shown to restore the normal kinematics of the shoulder in a laboratory setting. However, careful attention should be paid to the repair of the graft to the tuberosity, so that in case the primary procedure fails medially, the graft can still improve pain and function.